MAKNA PENDIDIKAN DALAM PENERAPAN PEMALI MENCAMPUR MAKANAN DARI RITUS RAMBU TUKA’ DAN RAMBU SOLO’ DAN RELEVANSINYA BAGI MASYARAKAT TORAJA - Yonathan Mangolo; Agustinus Karurukan Sampeasang; Riskayanti Pare Limbong (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Pemali mixing food in the ritual of rambu tuka' and rambu solo' is a ritual that is still accepted and maintained in Toraja society until now. The purpose of the study was to find out the meaning of education and the application of Pemali to mix food from the Rambu Tuka' and Rambu Solo' rituals in the life of the congregation. The method used to obtain information for this research is qualitative research through library research techniques, observation, as well as field research, in which the data that the authors get in the field are presented as they are. The results of this study, the authors prove that the meaning of education and the application of pemali to mix food from the Rambu Tuka' and Rambu Solo' ceremonies and its implications for the Toraja people, where in the meaning of pemali it turns out to contain the meaning of education which is to teach the values of obedience to grandmother's customs. Toraja people lead a harmonious life, but also as an effort to preserve these customs so that it is very important to carry out traditional education for the next generation. Pemali's mixing of food from the Rambu Tuka' and Rambu Solo' ceremonies turned out to be understood as a legacy from Aluk Todolo but has also been interpreted in the Christian sense as a traditional heritage in religious symbols that need to be preserved and preserved..